2018
DOI: 10.3389/fphys.2018.01093
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Spontaneous Brain Activity in Early Parkinson’s Disease With Mild Cognitive Impairment: A Resting-State fMRI Study

Abstract: Mild cognitive impairment (MCI) is a common symptom at the baseline of early Parkinson’s disease (PD) diagnosis, but the neural mechanism is unclear. To address the issue, the present study employed resting-state functional magnetic resonance imaging data of 19 drug-naïve PD patients with normal cognition (PD-NC), 10 PD patients with MCI (PD-MCI) and 13 age- and gender-matched healthy controls (HC) from the Parkinson’s progression markers initiative (PPMI) (http://www.ppmi-info.org/), and examined abnormal spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 52 publications
0
37
1
1
Order By: Relevance
“…In addition, studies have found that Parkinson's disease (PD), Huntington's disease, schizophrenia, major depressive disorder, type 2 diabetes mellitus (T2DM), chronic obstructive pulmonary disease (COPD), lung cancer following chemotherapy, hepatic encephalopathy, kidney deficiency syndrome, and other diseases can also cause CI (70)(71)(72)(73)(74)(75)(76)(77)(78)(79), but the relationships between these diseases and cognitive function and the pathogenesis of CI are still unknown, necessitating further in-depth studies. rs-fMRI will play an important role in the exploration of these unknown areas.…”
Section: Application Of Rs-fmri In Mild Traumatic Brain Injury (Mtbi)mentioning
confidence: 99%
“…In addition, studies have found that Parkinson's disease (PD), Huntington's disease, schizophrenia, major depressive disorder, type 2 diabetes mellitus (T2DM), chronic obstructive pulmonary disease (COPD), lung cancer following chemotherapy, hepatic encephalopathy, kidney deficiency syndrome, and other diseases can also cause CI (70)(71)(72)(73)(74)(75)(76)(77)(78)(79), but the relationships between these diseases and cognitive function and the pathogenesis of CI are still unknown, necessitating further in-depth studies. rs-fMRI will play an important role in the exploration of these unknown areas.…”
Section: Application Of Rs-fmri In Mild Traumatic Brain Injury (Mtbi)mentioning
confidence: 99%
“…Relative to routine ALFF (generally in the range of 0.01–0.1 Hz), it is more rational to depict brain activity by measuring the amplitude of spontaneous fluctuations at specific frequencies, and also in broader frequency bands [12]. Several studies found the frequency-dependent ALFF alterations in neuropsychiatric diseases, such as epilepsy, Parkinson’s disease, and insomnia [13-15]. These findings suggest that we should carefully consider the frequency-dependent effect on intrinsic local neuronal activity.…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous brain activity de cit in the left inferior frontal gyrus was restored in the PD patient after treatment [28]. Specially, the non-treatment PD-MCI group also exhibited increased ALFF in the inferior frontal gyrus [29]. And the increased activity in the inferior frontal gyrus was also found in the PD_MCI patients during performing a planning set-shifts task [30].…”
Section: Discussionmentioning
confidence: 85%